A perspective on architectural re-engineering - Barbosa, L. S. (2015)
Continuous evolution towards very large, heterogeneous, highly dynamic computing systems entails the need for sound and flexible approaches to deal with system modification and re-engineering. The approach proposed in this paper combines an analysis stage, to identify concrete patterns of interaction in legacy code, with an iterative re-engineering process at a higher level of abstraction. Both stages are supported by the tools CoordPat and Archery, respectively. Bi-directional model transformations connecting code level and design level architectural models are defined. The approach is demonstrated in a (fragment of a) case study.